2020
DOI: 10.1186/s12889-020-8286-8
|View full text |Cite
|
Sign up to set email alerts
|

Development of a fall-risk assessment profile for community-dwelling older adults by using the National Health Interview Survey in Taiwan

Abstract: Background: Falls represent a global health issue among older adults and cause a considerable burden on medical systems. In this study, a fall-risk assessment profile was developed for community-dwelling older adults. Method: The data of survey participants aged > 65 years were obtained from three rounds (2005, 2009, and 2013) of the National Health Interview Survey in Taiwan. In total, 8356 older participants were included in this study. Logistic regression analyses were used to determine potential predictors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 35 publications
(32 reference statements)
3
22
3
Order By: Relevance
“…28 In addition, previous studies suggest that those with impaired ADLs may lack confidence and have paradoxical experience of falls due to increased fear of falling. 8 The ADLs implied in this study were basic activities, which included mobility and selfcare difficulties. Our study found no association between IADL and falls as IADLs imply more complex activities related to independent living in the community such as managing finances and abilities to take medications.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…28 In addition, previous studies suggest that those with impaired ADLs may lack confidence and have paradoxical experience of falls due to increased fear of falling. 8 The ADLs implied in this study were basic activities, which included mobility and selfcare difficulties. Our study found no association between IADL and falls as IADLs imply more complex activities related to independent living in the community such as managing finances and abilities to take medications.…”
Section: Discussionmentioning
confidence: 99%
“…International studies have suggested a prevalence of falls of nearly 30% among older populations 10–12 . As for Asian countries, previous reports from Japan, 13 Taiwan 8 and Thailand 7 suggested a prevalence of falls 15.8%, 17.0% and 26.1% among their older populations respectively. Previous studies conducted in Malaysia have reported prevalence of 4.07%–32.8%.…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations